Analysis of Non-Tariff Measures Imposed by China and the United States on Brazilian Meat Complex Exports - Vasconcelos, Pâmela Soares; Pereira, Rafael Mesquita (Revista Economia Ensaios, 2025)
This study investigates the extent to which non-tariff measures (NTMs) imposed by China and the United States have affected Brazil’s meat complex exports between 2011 and 2022. Using coverage ratio and frequency index, the analysis quantifies the proportion of Brazilian meat exports subject to NTMs and compares the relative incidence across these two major trading partners. The results indicate a high concentration of trade barriers in this segment, with a larger number of notifications originating from China.